A meta-analysis of the relationship between self-assessment and Mathematics learning achievement - Hadi, Fransidha Sidhara; Arlinwibowo, Janu; Fatima, Gupita Nadindra (Jurnal Penelitian dan Evaluasi Pendidikan, 2023)
This study uses a meta-analysis model to describe the relationship between self-assessment and achievement in learning mathematics. This meta-analysis covers articles published from 2011 to 2022 and is restricted to studies published in English. Indexed articles by Google Scholar were chosen. The data must meet these criteria: quantitative research, containing correlational research on the relationship between self-assessment and mathematics learning achievement (including correlation values and sample size). Through the data screening process with predetermined criteria, 12 research results were obtained, containing 43 studies to be analyzed. This meta-analysis uses a random effect model due to the heterogeneous data distribution. A publication bias test was carried out with the Fail-safe N model to ensure the quality of the data. The result of the analysis showed that the data distribution was heterogeneous, according to the I2 test, so selecting the random effect model was the right decision. Regarding publication bias, an accurate Fail-safe N test shows that the data are free from publication bias. Thus, the analysis uses a suitable model, and the results of the analysis can be trusted. The total effect size indicates a significant positive correlation (r = 0.295) between self-assessment and students' mathematics achievement. Therefore, the higher the self-assessment index, the higher one's mathematics learning achievement.